DESEMPENHO TÉRMICO DE CRECHES PADRONIZADAS DO PROGRAMA PROINFÂNCIA EM DIFERENTES CIDADES ALAGOANAS - Araújo, Mayna; Scalco, Veridiana (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Building standardized designs without giving proper attention to climate conditions results in buildings with poor thermal performance and discomfort for the occupants, specially for school buildings, which are supposed to provide proper surroundings to a good learning experience. The present research aims to evaluate the influence of openings dimension, roof color and the use of ceiling fans on the thermal performance of standard day-care classrooms Type B from Projeto Proinfância in Maceió (East), Palmeira dos Índios (Agreste) and Pão de Açúcar (Sertão) in Alagoas. The analysis was conducted through computer simulations with the software Energyplus. The results show reductions up to 50% on annual percentage of discomfort hours in Maceió, 40% in Palmeira dos Índios and 35% in Pão de Açúcar, evidencing the impact of changes in openings typology and the importance of using roofs with low absorptance in warm climates. The use of ceiling fans proved to be a good strategy for all the cities. It was also noticed that, due to the semiarid climate of Pão de Açúcar, bioclimatic strategies such as nocturnal ventilation and thermal mass could also be used to obtain better results.